Enhancement of Health Services: Advanced Security Mechanism for Telemedicine in Public Health Practice - Biswas, Debarghya; Tiwari, Ankita (South Eastern European Journal of Public Health, 2024)
The sudden advancement of telemedicine in the healthcare industry presents potential hazards such as cyber-attacks and network susceptibilities, in addition to difficulties in patient privacy, data protection, and public health monitoring. To avoid illegal access, digital watermarking and precise medical image transfer are essential. Thus, for telemedicine in public health action, we introduce a unique security mechanism termed wavelet crypto fast decomposition with penguin optimization (WCFD-PO). Rivest-Shamir-Adelman (RSA), wavelet transforms (WT), and fast random singular value decomposition (FRSVD) encryption algorithms make up the suggested security methodology. By using the methods WT and FRSVD, one can decrease computing complexity and increase robustness. The PO approach offers a better-optimized scale factor in the fewest groups and repetitions as compared to the RSA approach, which is used for encrypting the watermarked image. The proposed mechanism is implemented by employing a Python application. Comprehensive testing indicates that our novel approach functions better than the current techniques, demonstrating the technique's higher efficiency. With the assistance of secure telemedicine solutions, this investigation offers physicians and tech programmers insightful information that will boost public health management.